Pengaruh Konseling Kelompok Pendekatan Realitas Terhadap Regulasi Emosi Siswa SMA Srijaya Negara Palembang - Rahmi Sofah; Talitha Sofie Azzahra (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
Abstract: This study aims to determine the effect of group counseling with a reality approach to emotion regulation in students at SMA Srijaya Negara Palembang. This research is a research using experimental research methods. The type of research design used is pre-experimental design. The pre-experimental design used is a one group pretest-posttest design. The subjects of this study were 10 students from class XI IPA 1 who were identified as having low emotional regulation. Data was collected using an emotional regulation questionnaire by distributing it to respondents using a Likert scale. Data analysis used the Wilcoxon test. The results of this study based on the SPSS output show that asymp.sig (2-tailed) has a value of 0.005. Because 0.005 is less than 0.05, Ho is rejected and Ha is accepted, which means that there is an average difference between the results of the pre-test and post-test emotion regulation. So that it can be said that there is a significant effect of group counseling with the reality approach on emotion regulation in students at SMA Srijaya Negara Palembang. Keywords: Emotion Regulation, Group Counseling, Reality Approach.